Taxonomic revision of Agraphydrus Régimbart, 1903 I. China and Taiwan (Coleoptera: Hydrophilidae: Acidocerinae) - Komarek, Albrecht; Hebauer, Franz (Zootaxa, 2018)
The species of Agraphydrus Régimbart, 1903 from China and Taiwan are revised. Nine species are redescribed and 33 new species are described: A. activus sp. n., A. agilis sp. n., A. arduus sp. n., A. audax sp. n., A. calvus sp. n., A. cantonensis sp. n., A. chinensis sp. n., A. comes sp. n., A. confusus sp. n., A. conicus sp. n., A. connexus sp. n., A. contractus sp. n., A. fasciatus sp. n., A. fikaceki sp. n., A. forcipatus sp. n., A. fujianensis sp. n., A. globipenis sp. n., A. gracilipalpis sp. n., A. igneus sp. n., A. jilanzhui sp. n., A. longipenis sp. n., A. niger sp. n., A. reductus sp. n., A. reticuliceps sp. n., A. robustus sp. n., A. schoenmanni sp. n., A. setifer sp. n., A. splendens sp. n., A. umbrosus sp. n., A. uncinatus sp. n., A. variabilis sp. n., A. wangmiaoi sp. n., and A. yunnanensis sp. n. Agraphydrus ryukyuensis (Matsui, 1994) is synonymized with A. coomani (Orchymont, 1927). The latter is recorded from China for the first time. A total of 42 species are now known from China and Taiwan. Agraphydrus orientalis (Orchymont, 1932) was erroneously recorded from China. Gymnhelochares Orchymont, 1932 is synonymized with Agraphydrus s. str. Régimbart, 1903. All species reviewed here are aquatic or occur in habitats near water. Species have been collected in a wide variety of flowing and stagnant water bodies, and four species are known to be hygropetric. Agraphydrus jilanzhui is exclusively found north of the Yangtze River; the other species occur south of it, with nine of them occurring on both sides. Eleven species covered here also occur outside of China and Taiwan. Habitus, male genitalia and morphological details are illustrated and a key to the species from China and Taiwan is added.